Sifat Kimia dan Organoleptik Permen Keras Sari Wortel (Daucus carota L.) dengan Penambahan Sari Buah Nanas (Ananas comosus L.) - Aprilya C. Johannes; Thelma D. J. Tuju; Christine F. Mamuaja (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
ABSTRACTThe purpose of this study was to determine the right concentration of pineapple juice addition to carrot juice hard candy. Knowing the chemical characteristic of carrot juice hard candy added with pineapple juice. Evaluating the panelist preference for carrot juice hard candy added with pineapple juice. This study used a completely randomized design (RAL) method consisting of 5 treatments and 3 replications of the addition of pineapple juice: (10%), (15%), (20%), (25%), (30%). Then chemical analysis was carried out to determine the water content, ash content and reducing sugar content and a organoleptic test. The results of this is the value of water content has an average of 1.47% - 3.10%, the value of ash content is 0,0120% - 0,0204% and the value of reducing sugar content is 11.42% - 13.63%. Carrot juice hard candy with the addition of 30% pineapple juice is the most preferred by panelist.Keywords: hard candy; carrot juice; pineapple juice.Â ABSTRAKTujuan dari penelitian ini adalah menentukan konsentrasi penambahan sari buah nanas yang tepat terhadap permen keras sari wortel, mengetahui sifat kimia permen keras sari wortel dan sari buah nanas, mengevaluasi tingkat kesukaan panelis terhadap permen keras sari wortel dan sari buah nanas. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) terdiri dari 5 perlakuan dan 3 ulangan perlakuan penambahan sari buah nanas sebanyak: (10%), (15%), (20%), (25%), (30%). Kemudian dilakukan analisis kimia untuk mengetahui kadar air, kadar abu dan kadar gula reduksi serta uji organoleptik. Hasil dari penelitian ini adalah nilai kadar air rata-rata 1,47%- 3,10%, nilai kadar abu 0,0120% - 0,0204% serta nilai kadar gula reduksi 11,42% - 13,63%.Â  Permen keras sari wortel dengan penambahan sari buah nanas 30% paling disukai panelis.Kata kunci: permen keras; sari wortel; sari buah nanas.